Multifunctional, three-dimensional tomography for analysis of eletrectrohydrodynamic jetting. (May 2015) - Nguyen, Xuan Hung; Gim, Yeonghyeon; Ko, Han Seo
Abstract: A three-dimensional optical tomography technique was developed to reconstruct three-dimensional objects using a set of two-dimensional shadowgraphic images and normal gray images. From three high-speed cameras, which were positioned at an offset angle of 45° between each other, number, size, and location of electrohydrodynamic jets with respect to the nozzle position were analyzed using shadowgraphic tomography employing multiplicative algebraic reconstruction technique (MART). Additionally, a flow field inside a cone-shaped liquid (Taylor cone) induced under an electric field was observed using a simultaneous multiplicative algebraic reconstruction technique (SMART), a tomographic method for reconstructing light intensities of particles, combined with three-dimensional cross-correlation. Various velocity fields of circulating flows inside the cone-shaped liquid caused by various physico-chemical properties of liquid were also investigated. Highlights: We develop the three-dimensional optical tomography technique. We analyze the electrohydrodynamic jet using multiple high-speed cameras by the MART. The flow field inside the cone-shaped liquid under the electric field is observed. Various velocity fields of circulating flows of liquid are investigated. The developed tomographic PIV reconstructs the complex circulating flow.